PENTINGNYA MATERIALITAS PADA PROSEDUR AUDIT VOUCHING TRANSAKSI PENJUALAN - Emy Nurmalasari; Endah Susilowati (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Materiality plays an important role in deciding the relevance of the financial information displayed and is the basis for an auditor in knowing the focus of the audit. The importance of determining materiality can also be used in audit procedures, one of which is sales transaction vouching. This study aims to explain the important role of materiality in the sales transaction vouching audit procedure to carry out a quality audit process. The research method used in this research is a qualitative approach through descriptive analysis. The data collection techniques included observation and interviews with one senior auditor about the importance of materiality in the sales transaction vouching procedure. The results showed that materiality has an important role in the vouching audit procedure to focus on matters that have an impact on the financial statements thereby increasing audit efficiency. Audit efficiency is an effort to conduct audits using available resources effectively and efficiently. Auditors can more easily perform audits on sales transactions through vouching by considering materiality.